Customer Brand Attachment and Engagement Among Online Retail Customers in Beijing, China - ​Yu, Rongwei (Pacific International Journal, 2025)
This study examines customer brand attachment and engagement among online retail customers in Beijing, China, using a quantitative comparative correlational design with 380 respondents. Findings reveal moderate brand attachment across emotional bonding, cognitive connection, and trust, with male and younger customers (25-45 years) showing stronger connections. Engagement levels were highest in social interaction but lowest in behavioral activation, indicating customers enjoy community participation but are less inclined toward frequent purchases or advocacy. Trust emerged as a key driver of cognitive, emotional, and social engagement, though it did not significantly influence purchasing behavior. Demographic variations highlight the need for tailored strategies: younger "Explorer" customers exhibited higher behavioral engagement, while Loyalists demonstrated deeper. The study recommends personalized experiences to strengthen emotional attachment, transparent communication to build trust, and incentive-based loyalty programs to boost active purchasing. By leveraging social interaction strengths and addressing demographic-specific engagement gaps, brands can enhance customer relationships in competitive e-commerce markets. These insights provide actionable recommendations for optimizing engagement strategies and fostering sustainable brand loyalty.